A flexible, wrinkled and stretchable metal current collector and its preparation method and application
By using flexible pleat stretchable metal current collector in lithium-ion batteries, the metal layer and the flexible substrate are closely contacted by semi-coagulation and evaporation technology, the dendrite problem caused by uneven lithium deposition is solved, and the circulation performance of the battery is improved. Security.
Patent Information
- Application Number
- CN202410469099.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-18
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-04-18
AI Technical Summary
Uneven deposition of metal lithium during the charge and discharge cycle leads to uneven accumulation of internal stress, resulting in tip deposition effect and lithium dendrites, affecting battery performance and safety.
Flexible pleated stretchable metal current collector is used, which consists of a flexible base layer, a semi-solidified PDMS layer and a metal layer. The metal layer and the flexible base are in close contact through the semi-solidified evaporation method, release stress during lithium deposition, and suppress lithium Generation of dendrites.
The uniform deposition of lithium is achieved, the generation of dendrites is inhibited, the circulation performance and safety of the battery are improved, and the efficiency and cycle life of the Coulomb is improved.
Smart Images

Figure CN118352534B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of energy storage batteries, and in particular relates to a flexible, wrinkled and stretchable metal current collector and a preparation method and application thereof. Background Art
[0002] Metal lithium has a high theoretical capacity (3860 mAh g -1 ), low redox potential (-3.040 V·vs standard hydrogen electrode potential) and extremely low density (0.59 g·cm -3 ) and other advantages, and is considered to be a good negative electrode material for high energy density batteries. However, when lithium is used as the negative electrode, during the charge and discharge cycle, the uneven deposition of lithium will lead to the uneven accumulation of internal stress and then the tip deposition effect, so that lithium will be deposited preferentially at the tip, and lithium dendrites will be generated. Lithium dendrites have a great influence on the performance of the battery. First, the growth of dendrites will cause some dendrites to begin to dissolve from the waist and root first. The top of the dendrite will dissolve and fall off from the current collector over time to form dead lithium. These dead lithiums will not contribute to the capacity during the battery cycle, but will cause the theoretical capacity of the battery to decrease, and will also reduce the battery cycle life. Secondly, when the dendrites grow to a certain extent, they will pierce the diaphragm, causing the positive and negative electrodes of the battery to directly contact, causing the battery to short-circuit and release huge heat, leading to explosion, which has great safety hazards. To this end, the present invention proposes a method for preparing a flexible, wrinkled and stretchable metal current collector. Summary of the invention
[0003] In order to solve the above technical problems, the present invention proposes a flexible wrinkled stretchable metal current collector and its preparation method and application. The current collector prepared by the present invention has a flexible substrate, which can release the stress accumulated by lithium during the deposition process, make lithium deposit evenly, inhibit the formation of lithium dendrites, and improve the cycle performance and safety of the battery; and use a semi-solidification evaporation method to make the metal layer in close contact with the flexible substrate to improve its mechanical properties and reduce the contact resistance between the metal layer and the substrate. Compared with direct thermal evaporation that adheres to the surface of the PDMS substrate, part of the metal substrate will be embedded in the PDMS in the semi-solidification method, which improves the bonding performance between the coating and the PDMS.
[0004] To achieve the above object, the present invention provides the following technical solutions:
[0005] One of the technical solutions of the present invention:
[0006] A flexible wrinkled and stretchable metal current collector comprises a flexible substrate layer, a semi-solidified PDMS layer and a metal layer which are sequentially arranged from bottom to top.
[0007] Furthermore, the flexible base layer is a flexible polymer substrate, preferably an epoxy resin, polyurethane, or PDMS substrate, and the thickness of the flexible base layer is 100-200 μm.
[0008] Furthermore, the raw material of the metal layer is gold, silver, copper, iron, nickel, aluminum and alloys thereof, and the thickness is 1-5 μm.
[0009] In the flexible wrinkled stretchable metal current collector of the present invention, a metal layer is adhered to the upper surface of the semi-solidified PDMS layer, and the metal layer is directly used as a current collector without other current collectors. The ultra-thin metal layer is tightly adhered to the surface of the soft semi-solidified PDMS layer, and a flexible current collector structure can be formed in this way. By releasing the stress accumulated by the deposition of lithium during the charge and discharge cycle, the uneven deposition of lithium at a certain point due to uneven stress distribution is avoided, thereby forming a tip effect to cause the formation and growth of dendrite lithium. The flexible current collector of the present invention can form wrinkles to release stress during the deposition process, and achieve the effect of inhibiting dendrite lithium. In addition, the close fit between the metal layer and the semi-solidified PDMS layer can not only maintain good flexibility, but also reduce the contact resistance between them, and can form a good conductive layer of the current collector.
[0010] The second technical solution of the present invention:
[0011] A method for preparing the flexible, wrinkled and stretchable metal current collector comprises the following steps:
[0012] The flexible polymer substrate is cut into discs, PDMS glue is spin-coated onto one side of the disc-shaped flexible polymer substrate, and dried to obtain a flexible base layer carrying a semi-solidified PDMS layer. A metal particle target material is then deposited on the surface of the semi-solidified PDMS layer to form a metal layer, thereby obtaining the flexible wrinkled stretchable metal current collector.
[0013] Furthermore, the spin coating amount of the PDMS glue on the disc-shaped flexible polymer substrate with a diameter of 9-12 mm is 3-6 g.
[0014] Furthermore, the flexible polymer substrate is sliced using a microtome.
[0015] Furthermore, the PDMS glue is prepared from a main agent and a curing agent in a mass ratio of 9:1.
[0016] Furthermore, the spin coating speed is 1000 rpm and the time is 30 s.
[0017] Furthermore, the drying process is carried out at a temperature of 60-80°C and for a time of 2-3 hours.
[0018] Furthermore, the deposition method includes one of atomic layer deposition, magnetron sputtering, thermal evaporation or water electroplating.
[0019] The present invention deposits an ultra-thin metal layer through atomic layer deposition, magnetron sputtering, thermal evaporation and other technologies, and closely connects the metal layer with a semi-solidified PDMS layer to form an integrated current collector structure, thereby reducing the contact resistance between them; the semi-solidified PDMS glue is deposited to obtain a composite electrode with ultra-high mechanical strength, and the mechanical properties are improved by 3-5 times compared with direct deposition on a flexible polymer substrate while ensuring conductivity; the flexible polymer substrate and the ultra-thin metal layer with good adhesion can release the stress accumulated on the electrode due to the uneven deposition of lithium during the charge and discharge process, thereby inducing uniform lithium deposition, inhibiting the formation of dendrites, and improving the safety and service life of the battery.
[0020] The third technical solution of the present invention:
[0021] The application of the flexible wrinkled stretchable metal current collector in lithium ion batteries.
[0022] Furthermore, the flexible wrinkled stretchable metal current collector is used as a negative electrode of a lithium-ion battery.
[0023] Compared with the prior art, the present invention has the following advantages and technical effects:
[0024] (1) The present invention uses a flexible polymer as a substrate, and utilizes its good flexibility and stretchability to release the stress accumulated thereon; secondly, the flexible polymer substrate has excellent corrosion resistance, a high dielectric constant, and can maintain its stability over a wide temperature range (-60~200°C), so it can withstand thermal evaporation and serve as a thermally stable device substrate material or electrode material;
[0025] The metal layer of the present invention adheres to the semi-solidified PDMS layer to form an integrated metal negative electrode current collector. On the basis of ensuring conductivity, compared with direct thermal evaporation on a flexible polymer substrate, the mechanical properties can be improved by 3-5 times, and the direct contact resistance between the metal layer and the polymer substrate is greatly reduced.
[0026] (2) The flexible wrinkled stretchable metal current collector of the present invention is formed by adhering a metal layer on the upper surface of the semi-solidified PDMS layer. The ultra-thin metal layer is tightly adhered to the surface of the soft semi-solidified PDMS layer. In this way, a flexible current collector structure can be formed. By utilizing good flexibility and stretchability, the stress accumulated by lithium during the charge and discharge cycle deposition process is released, thereby allowing lithium to be deposited evenly, thereby inhibiting the formation of lithium dendrites and further improving the coulombic efficiency and cycle life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0028] Figure 1 This is a schematic diagram of preparing a flexible, wrinkled and stretchable metal current collector according to Example 1 of the present invention;
[0029] Figure 2 This is a surface morphology of the flexible, wrinkled and stretchable metal current collector prepared in Example 1 of the present invention;
[0030] Figure 3 This is a surface morphology image of the flexible wrinkled stretchable metal current collector of Example 1 of the present invention after being stretched 50% and recovered once;
[0031] Figure 4 This is a surface morphology image of the flexible wrinkled stretchable metal current collector of Example 1 of the present invention after being stretched 50% ten times and recovered. DETAILED DESCRIPTION
[0032] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0033] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0034] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0035] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0036] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0037] An embodiment of the present invention provides a flexible, wrinkled and stretchable metal current collector, comprising a flexible substrate layer, a semi-solidified PDMS layer and a metal layer arranged in sequence from bottom to top.
[0038] In a preferred embodiment of the present invention, the flexible base layer is a flexible polymer substrate, including epoxy resin, polyurethane, PDMS substrate, and the thickness of the flexible base layer is 100-200 μm. More preferably, the flexible polymer substrate is a PDMS substrate purchased from Hangzhou Weisichuang Technology, with a thickness of 100 μm.
[0039] In a preferred embodiment of the present invention, the raw material of the metal layer is one or more of gold, silver, copper, iron, nickel, aluminum and alloys thereof, and the thickness is 1-5 μm. More preferably, the raw material of the metal layer is copper, and the thickness is 1.5 μm.
[0040] If the flexible base layer is too thin, it will be too fragile and unable to serve as a substrate, and will be easily damaged. If it is too thick, the overall thickness of the electrode will increase, increasing the internal impedance of the battery. If the metal layer is too thin, it will not be possible to ensure the successful and complete deposition of the metal. If it is too thick, excessive stress will accumulate during the deposition process, causing cracking.
[0041] The embodiment of the present invention further provides a method for preparing the flexible, wrinkled and stretchable metal current collector, comprising the following steps:
[0042] The flexible polymer substrate is cut into discs, PDMS glue is spin-coated onto one side of the disc-shaped flexible polymer substrate, and dried to obtain a flexible base layer carrying a semi-solidified PDMS layer. A metal particle target material is then deposited on the surface of the semi-solidified PDMS layer to form a metal layer, thereby obtaining the flexible wrinkled stretchable metal current collector.
[0043] In a preferred embodiment of the present invention, the flexible polymer substrate is cut into discs with a diameter of 9-12 mm, preferably a diameter of 10 mm, and the flexible polymer substrate is sliced using a slicer.
[0044] In a preferred embodiment of the present invention, the amount of the PDMS glue spin-coated on the flexible polymer substrate is 3-6 g, more preferably 5 g.
[0045] In a preferred embodiment of the present invention, the PDMS glue is prepared by mixing a main agent and a curing agent in a mass ratio of 9:1, wherein the curing agent is polydimethylsiloxane with a hydrogen group, and the main agent is polydimethylsiloxane with a vinyl active group.
[0046] More specifically, the PDMS glue used in the embodiment of the present invention is Dow Corning DC184, which was purchased from Shenzhen Songsen New Material Technology Co., Ltd.
[0047] In a preferred embodiment of the present invention, the spin coating speed is 1000 rpm and the time is 30 s.
[0048] In a preferred embodiment of the present invention, the temperature of the drying treatment is 60-80°C and the time is 2-3 hours. More preferably, the temperature of the drying treatment is 80°C and the time is 2 hours.
[0049] If the drying time is too long or the temperature is too high, the PDMS will solidify directly and will not have the effect of a semi-solidified layer, which is the same as directly depositing it on a flexible substrate. If the drying time is too short or the temperature is too low, the PDMS will be in a gel state and will not be able to adhere well to the flexible substrate, and the subsequent deposition steps cannot be completed.
[0050] In a preferred embodiment of the present invention, the deposition method includes one of atomic layer deposition, magnetron sputtering, thermal evaporation or water electroplating, and thermal evaporation is more preferred.
[0051] Atomic layer deposition, magnetron sputtering, thermal evaporation or water electroplating are all conventional technical means in this field, and the specific process will not be described in detail. It is only necessary to deposit the metal particle target on the surface of the semi-solidified PDMS layer to reach the required thickness.
[0052] As a preferred embodiment of the present invention, the thermal evaporation is carried out at 10 -5 The evaporation was carried out under a vacuum degree of 1.3 Pa and the evaporation rate was 0.3Å / s. Too high a rate would cause cracks on the sample surface, while too low a rate would take too long.
[0053] The embodiment of the present invention also provides the application of the flexible, wrinkled and stretchable metal current collector in a lithium-ion battery. Furthermore, the flexible, wrinkled and stretchable metal current collector is used as the negative electrode of the lithium-ion battery.
[0054] The technical solution of the present invention is further illustrated by the following embodiments.
[0055] Example 1
[0056] (1) Select a slicing mold with a specification of 10 mm, place the PDMS substrate in a slicer, and cut to obtain a circular PDMS substrate;
[0057] (2) Stir 5 g of PDMS glue evenly and place it in a vacuum box for 30 min to remove bubbles generated during stirring;
[0058] (3) removing the protective film on the surface of the disc-shaped PDMS substrate obtained in step (1) and keeping the PDMS surface clean;
[0059] (4) The disc-shaped PDMS substrate obtained in step (3) is sucked onto a spin coater, and the PDMS glue obtained in step (2) is spin-coated on one side of the disc-shaped PDMS substrate at a spin coating speed of 1000 rpm for 30 seconds, until a layer of the PDMS glue can be clearly seen on the PDMS substrate;
[0060] (5) placing the sample spin-coated in step (4) in a vacuum drying oven and drying at a temperature of 80° C. for 2 h until the PDMS glue is solidified into a gel, thereby obtaining a flexible substrate layer carrying a semi-solidified PDMS layer;
[0061] (6) Place the flexible substrate layer carrying the semi-solidified PDMS layer obtained in step (5) into the sample chamber of the thermal evaporation chamber, place the copper target in the sample chamber, and -5 Pa, evaporation was started at an evaporation rate of 0.3Å / s for 3h;
[0062] (7) Repeat step (6) to obtain a copper metal layer with a thickness of 1.5 μm, and obtain a flexible wrinkled stretchable metal current collector (see surface morphology). Figure 2 ).
[0063] The surface morphology of the flexible wrinkled stretchable metal current collector of Example 1 of the present invention after being stretched by 50% (i.e., the stretched length is 50% of the original length of the flexible wrinkled stretchable metal current collector, the same below) after one recovery is shown in FIG. Figure 3 , the surface morphology after stretching 50% and recovering ten times is shown in Figure 4 , it can be seen that the current collector recovers to the morphology before stretching, and there is no obvious cracking on the surface.
[0064] The schematic diagram of the preparation of the flexible wrinkled stretchable metal current collector of Example 1 of the present invention is shown in Figure 1 .
[0065] The flexible, wrinkled, stretchable metal current collector obtained in Example 1 was stretched by 30%, and its terminal resistance was measured to be 1.1Ω.
[0066] The battery model was selected as a 2032-type button battery. The flexible wrinkled stretchable metal current collector stretched by 30% in Example 1 was assembled in the battery as the positive electrode, and the lithium sheet was used as the negative electrode. 1 mAh·cm -2 The capacity of lithium was transferred to a flexible wrinkled stretchable metal current collector to obtain a lithium negative electrode sheet, and the cycle was set to 100 times. The coulombic efficiency of the tested battery was 98.34%.
[0067] The flexible, wrinkled, stretchable metal current collector obtained in Example 1 was stretched by 50%, and its terminal resistance was measured to be 1.4Ω.
[0068] The battery model was selected as a 2032-type button battery. The flexible wrinkled stretchable metal current collector of Example 1, which was stretched by 50%, was assembled in the battery as the positive electrode, and the lithium sheet was used as the negative electrode. 1 mAh·cm -2 The lithium negative electrode was obtained by transferring the lithium with high capacity to the flexible wrinkled stretchable metal current collector, and the cycle was set to 100 times. The coulombic efficiency of the tested battery was 98.22%.
[0069] The flexible wrinkled stretchable metal current collector obtained in Example 1 was stretched by 50%, and the stretching was repeated ten times. The terminal resistance was measured to be 30.8Ω.
[0070] The battery model was selected as a 2032-type button battery. The flexible wrinkled stretchable metal current collector of Example 1 was stretched by 50% and repeatedly stretched ten times as the positive electrode and assembled in the battery. The lithium sheet was used as the negative electrode and 1 mAh cm was deposited. -2 The capacity of lithium was transferred to a flexible wrinkled stretchable metal current collector to obtain a lithium negative electrode sheet, and the cycle was set to 100 times. The coulombic efficiency of the tested battery was 96.32%.
[0071] In summary, it is proved that the flexible wrinkled stretchable metal current collector obtained in Example 1 has a good Coulombic efficiency.
[0072] Comparative Example 1
[0073] The same as Example 1, except that the semi-solidified PDMS layer is omitted, specifically:
[0074] (1) Select a slicing mold with a specification of 10 mm, place the PDMS substrate in a slicer, and cut to obtain a circular PDMS substrate;
[0075] (2) removing the protective film on the surface of the disc-shaped PDMS substrate obtained in step (1) and keeping the PDMS surface clean;
[0076] (3) Place the disc-shaped PDMS substrate obtained in step (2) into the sample chamber of the thermal evaporation chamber, place the copper target in the sample chamber, and -5 Pa, evaporation was started at an evaporation rate of 0.3Å / s for 3h;
[0077] (4) Repeat step (6) to obtain a copper metal layer with a thickness of 1.5 μm to obtain a metal current collector.
[0078] The metal current collector obtained in Comparative Example 1 was stretched by 30%, and its terminal resistance was measured to be 30Ω.
[0079] The battery model was selected as a 2032 button battery. The flexible wrinkled stretchable metal current collector of comparative example 1 stretched by 30% was assembled as the positive electrode in the battery, and the lithium sheet was used as the negative electrode. 1 mAh·cm-2 The capacity of lithium was transferred to a flexible wrinkled stretchable metal current collector to obtain a lithium negative electrode sheet, and the cycle was set to 100 times. The coulombic efficiency of the tested battery was 96.56%.
[0080] The metal current collector obtained in Comparative Example 1 was stretched by 50%, and its terminal resistance was measured to be 35Ω.
[0081] The battery model was selected as a 2032 button battery. The flexible wrinkled stretchable metal current collector stretched by 50% in comparative example 1 was assembled into the battery as the positive electrode, and the lithium sheet was used as the negative electrode. 1 mAh·cm -2 The capacity of lithium was transferred to a flexible wrinkled stretchable metal current collector to obtain a lithium negative electrode sheet, and the cycle was set to 100 times. The coulombic efficiency of the tested battery was 93.42%.
[0082] The metal current collector obtained in Comparative Example 1 was stretched by 50%, and the stretching was repeated ten times. The terminal resistance was measured to be 500Ω.
[0083] The battery model was selected as a 2032-type button battery. The comparative example 1 was stretched by 50%. After repeated stretching ten times, the flexible wrinkled stretchable metal current collector was assembled in the battery as the positive electrode, and the lithium sheet was used as the negative electrode. 1 mAh cm -2 The capacity of lithium is transferred to a flexible wrinkled stretchable metal current collector to obtain a lithium negative electrode sheet, and the cycle is set to 100 times. The coulombic efficiency of the tested battery is less than 50%.
[0084] Comparing the data of Example 1 with Comparative Example 1, it is proved that the use of semi-solidified PDMS layer evaporation can better integrate the metal layer with the PDMS substrate, thereby obtaining a lower contact resistance.
[0085] Example 2
[0086] (1) Select a slicing mold with a specification of 10 mm, place the PDMS substrate in a slicer, and cut to obtain a circular PDMS substrate;
[0087] (2) Stir 5 g of PDMS glue evenly and place it in a vacuum box for 30 min to remove bubbles generated during stirring;
[0088] (3) removing the protective film on the surface of the disc-shaped PDMS substrate obtained in step (1) and keeping the PDMS surface clean;
[0089] (4) The disc-shaped PDMS substrate obtained in step (3) is sucked onto a spin coater, and the PDMS glue obtained in step (2) is spin-coated on one side of the disc-shaped PDMS substrate at a spin coating speed of 1000 rpm for 30 seconds, until a layer of the PDMS glue can be clearly seen on the PDMS substrate;
[0090] (5) placing the sample spin-coated in step (4) in a vacuum drying oven and drying at a temperature of 80° C. for 2 h until the PDMS glue is solidified into a gel, thereby obtaining a flexible substrate layer carrying a semi-solidified PDMS layer;
[0091] (6) performing atomic layer deposition on the flexible substrate layer carrying the semi-solidified PDMS layer obtained in step (5);
[0092] (7) Repeat step (6) to obtain a copper metal layer with a thickness of 1.5 μm, thereby obtaining a flexible wrinkled stretchable metal current collector.
[0093] The flexible, wrinkled, stretchable metal current collector obtained in Example 2 was stretched by 50%, and its terminal resistance was measured to be 1.5Ω.
[0094] The battery model was selected as a 2032-type button battery. The flexible wrinkled stretchable metal current collector stretched 50% in Example 2 was assembled in the battery as the positive electrode, and the lithium sheet was used as the negative electrode. 1 mAh·cm -2 The capacity of lithium was transferred to a flexible, wrinkled, stretchable metal current collector to obtain a lithium negative electrode sheet, and the cycle was set to 100 times. The coulombic efficiency of the tested battery was 98.13%, proving that the flexible, wrinkled, stretchable metal current collector obtained in Example 2 has a good coulombic efficiency.
[0095] Comparative Example 2
[0096] The same as Example 2, except that the semi-solidified PDMS layer is omitted, specifically:
[0097] (1) Select a slicing mold with a specification of 10 mm, place the PDMS substrate in a slicer, and cut to obtain a circular PDMS substrate;
[0098] (2) removing the protective film on the surface of the disc-shaped PDMS substrate obtained in step (1) and keeping the PDMS surface clean;
[0099] (3) performing atomic layer deposition on the disc-shaped PDMS substrate obtained in step (2);
[0100] (4) Repeat step (6) to obtain a copper metal layer with a thickness of 1.5 μm to obtain a metal current collector.
[0101] The flexible wrinkled stretchable metal current collector obtained in Comparative Example 2 was stretched by 50%, and its terminal resistance was measured to be 36.4Ω.
[0102] The battery model was selected as a 2032 button battery. The flexible wrinkled stretchable metal current collector of comparative example 2 stretched by 50% was assembled as the positive electrode in the battery, and the lithium sheet was used as the negative electrode. 1 mAh cm -2The capacity of lithium was transferred to a flexible wrinkled stretchable metal current collector to obtain a lithium negative electrode sheet, and the cycle was set to 100 times. The coulombic efficiency of the tested battery was 92.69%.
[0103] Comparing the data of Example 2 with Comparative Example 2, it is proved that the use of atomic layer deposition of the semi-solidified PDMS layer can better integrate the metal layer with the PDMS substrate, thereby obtaining a lower contact resistance.
[0104] Example 3
[0105] (1) Select a slicing mold with a specification of 10 mm, place the PDMS substrate in a slicer, and cut to obtain a circular PDMS substrate;
[0106] (2) Stir 5 g of PDMS glue evenly and place it in a vacuum box for 30 min to remove bubbles generated during stirring;
[0107] (3) removing the protective film on the surface of the disc-shaped PDMS substrate obtained in step (1) and keeping the PDMS surface clean;
[0108] (4) The disc-shaped PDMS substrate obtained in step (3) is sucked onto a spin coater, and the PDMS glue obtained in step (2) is spin-coated on one side of the disc-shaped PDMS substrate at a spin coating speed of 1000 rpm for 30 seconds, until a layer of the PDMS glue can be clearly seen on the PDMS substrate;
[0109] (5) placing the sample spin-coated in step (4) in a vacuum drying oven and drying at a temperature of 80° C. for 2 h until the PDMS glue is solidified into a gel, thereby obtaining a flexible substrate layer carrying a semi-solidified PDMS layer;
[0110] (6) subjecting the flexible substrate layer carrying the semi-solidified PDMS layer obtained in step (5) to magnetron sputtering;
[0111] (7) Repeat step (6) to obtain a copper metal layer with a thickness of 1.5 μm, thereby obtaining a flexible wrinkled stretchable metal current collector.
[0112] The flexible, wrinkled, stretchable metal current collector obtained in Example 3 was stretched by 50%, and its terminal resistance was measured to be 1.2Ω.
[0113] The battery model was selected as a 2032-type button battery. The flexible wrinkled stretchable metal current collector stretched by 50% in Example 3 was assembled in the battery as the positive electrode, and the lithium sheet was used as the negative electrode. 1 mAh·cm -2The capacity of lithium was transferred to a flexible, wrinkled, stretchable metal current collector to obtain a lithium negative electrode sheet, and the cycle was set to 100 times. The coulombic efficiency of the tested battery was 98.33%, proving that the flexible, wrinkled, stretchable metal current collector obtained in Example 3 has a good coulombic efficiency.
[0114] Comparative Example 3
[0115] The same as Example 3, except that the semi-solidified PDMS layer is omitted, specifically:
[0116] (1) Select a slicing mold with a specification of 10 mm, place the PDMS substrate in a slicer, and cut to obtain a circular PDMS substrate;
[0117] (2) removing the protective film on the surface of the disc-shaped PDMS substrate obtained in step (1) and keeping the PDMS surface clean;
[0118] (3) subjecting the disc-shaped PDMS substrate obtained in step (2) to magnetron sputtering;
[0119] (4) Repeat step (6) once to obtain a copper metal layer with a thickness of 1.5 μm to obtain a metal current collector.
[0120] The flexible wrinkled stretchable metal current collector obtained in Comparative Example 3 was stretched by 50%, and its terminal resistance was measured to be 30Ω.
[0121] The battery model was selected as a 2032 button battery. The flexible wrinkled stretchable metal current collector stretched by 50% in comparative example 3 was assembled in the battery as the positive electrode, and the lithium sheet was used as the negative electrode. 1 mAh cm -2 The capacity of lithium was transferred to a flexible wrinkled stretchable metal current collector to obtain a lithium negative electrode sheet, and the cycle was set to 100 times. The coulombic efficiency of the tested battery was 93.56%.
[0122] Comparing the data of Example 3 with Comparative Example 3, it is proved that magnetron sputtering of the semi-solidified PDMS layer can better integrate the metal layer with the PDMS substrate, thereby obtaining a lower contact resistance.
[0123] Example 4
[0124] (1) Select a slicing mold with a specification of 10 mm, place the PDMS substrate in a slicer, and cut to obtain a circular PDMS substrate;
[0125] (2) Stir 5 g of PDMS glue evenly and place it in a vacuum box for 30 min to remove bubbles generated during stirring;
[0126] (3) removing the protective film on the surface of the disc-shaped PDMS substrate obtained in step (1) and keeping the PDMS surface clean;
[0127] (4) The disc-shaped PDMS substrate obtained in step (3) is sucked onto a spin coater, and the PDMS glue obtained in step (2) is spin-coated on one side of the disc-shaped PDMS substrate at a spin coating speed of 1000 rpm for 30 seconds, until a layer of the PDMS glue can be clearly seen on the PDMS substrate;
[0128] (5) placing the sample spin-coated in step (4) in a vacuum drying oven and drying at a temperature of 60° C. for 2 h until the PDMS glue is solidified into a gel, thereby obtaining a flexible substrate layer carrying a semi-solidified PDMS layer;
[0129] (6) depositing a thin layer of copper on the flexible substrate layer carrying the semi-solidified PDMS layer obtained in step (5) by magnetron sputtering, and then increasing the thickness of the copper layer to 1.5 μm by water electroplating to obtain a flexible wrinkled stretchable metal current collector;
[0130] The flexible, wrinkled, stretchable metal current collector obtained in Example 4 was stretched by 50%, and its terminal resistance was measured to be 2Ω.
[0131] The battery model was selected as a 2032-type button battery. The flexible wrinkled stretchable metal current collector stretched by 50% in Example 4 was assembled in the battery as the positive electrode, and the lithium sheet was used as the negative electrode. 1 mAh·cm -2 The capacity of lithium was transferred to a flexible, wrinkled, stretchable metal current collector to obtain a lithium negative electrode sheet, and the cycle was set to 100 times. The coulombic efficiency of the tested battery was 97.69%, proving that the flexible, wrinkled, stretchable metal current collector obtained in Example 4 has a good coulombic efficiency.
[0132] Comparative Example 4
[0133] The same as Example 4, except that the semi-solidified PDMS layer is omitted, specifically:
[0134] (1) Select a slicing mold with a specification of 10 mm, place the PDMS substrate in a slicer, and cut to obtain a circular PDMS substrate;
[0135] (2) removing the protective film on the surface of the disc-shaped PDMS substrate obtained in step (1) and keeping the PDMS surface clean;
[0136] (3) A thin layer of copper is deposited on the semi-solidified PDMS layer obtained in step (2) by magnetron sputtering, and then the thickness of the copper layer is increased to 1.5 μm by water electroplating to obtain a metal current collector.
[0137] The flexible wrinkled stretchable metal current collector obtained in Comparative Example 4 was stretched by 50%, and its terminal resistance was measured to be 37.5Ω.
[0138] The battery model was selected as a 2032 button battery. The flexible wrinkled stretchable metal current collector of comparative example 4 stretched by 50% was assembled as the positive electrode in the battery, and the lithium sheet was used as the negative electrode. 1 mAh cm -2 The capacity of lithium was transferred to a flexible wrinkled stretchable metal current collector to obtain a lithium negative electrode sheet, and the cycle was set to 100 times. The coulombic efficiency of the tested battery was 92.79%.
[0139] Comparing the data of Example 4 with Comparative Example 4, it is proved that the use of water electroplating of the semi-solidified PDMS layer can better integrate the metal layer with the PDMS substrate, thereby obtaining a lower contact resistance.
[0140] Comparative Example 5
[0141] The same as Example 1, except that the drying temperature in step (5) is 40° C. and the drying time is 3 h.
[0142] If the temperature is too low, the PDMS glue is still in a gel state and cannot adhere to the flexible substrate, so subsequent experimental steps cannot be performed.
[0143] Comparative Example 6
[0144] The same as Example 1, except that the drying temperature in step (5) is 100° C. and the drying time is 3 h.
[0145] If the temperature is too high, the PDMS glue will solidify directly, which is the same as depositing it directly on the PDMS.
[0146] Comparative Example 7
[0147] The same as Example 1, except that in step (7), a copper metal layer with a thickness of 10 μm is obtained.
[0148] If the copper layer is too thick, the semi-solidified PDMS will crack directly.
[0149] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A flexible, wrinkled and stretchable metal current collector, characterized in that: It includes a flexible base layer, a semi-solidified PDMS layer and a metal layer which are arranged in sequence from bottom to top; The raw material of the metal layer is copper, and the thickness is 1.5 μm; The method for preparing the flexible wrinkled stretchable metal current collector comprises the following steps: The flexible polymer substrate is cut into a disc shape, PDMS glue is spin-coated onto one side of the disc-shaped flexible polymer substrate, and a flexible base layer carrying a semi-solidified PDMS layer is obtained by drying, and then a metal particle target material is deposited on the surface of the semi-solidified PDMS layer to form a metal layer, thereby obtaining the flexible wrinkled stretchable metal current collector; The amount of the PDMS glue spin-coated on a circular flexible polymer substrate with a diameter of 9-12 mm is 3-6 g; The spin coating speed is 1000 rpm and the time is 30 s; The drying temperature is 60-80°C and the time is 2-3h; The deposition method includes one of atomic layer deposition, magnetron sputtering, thermal evaporation or water electroplating.
2. The flexible, wrinkled and stretchable metal current collector according to claim 1, characterized in that: The flexible base layer is a flexible polymer substrate with a thickness of 100-200 μm.
3. A method for preparing a flexible, wrinkled and stretchable metal current collector according to any one of claims 1 to 2, characterized in that: The following steps are involved: The flexible polymer substrate is cut into a disc shape, PDMS glue is spin-coated onto one side of the disc-shaped flexible polymer substrate, and a flexible base layer carrying a semi-solidified PDMS layer is obtained by drying, and then a metal particle target material is deposited on the surface of the semi-solidified PDMS layer to form a metal layer, thereby obtaining the flexible wrinkled stretchable metal current collector; The amount of the PDMS glue spin-coated on a circular flexible polymer substrate with a diameter of 9-12 mm is 3-6 g; The spin coating speed is 1000 rpm and the time is 30 s; The drying temperature is 60-80°C and the time is 2-3h; The deposition method includes one of atomic layer deposition, magnetron sputtering, thermal evaporation or water electroplating.
4. Application of the flexible, wrinkled and stretchable metal current collector according to any one of claims 1 to 2 in a lithium-ion battery.
Citation Information
Patent Citations
Elastic current collector, preparation method of elastic current collector, battery electrode plate, and flexible lithium ion battery
CN108155387A
Preparation method of omnidirectional stretchable conductive film
CN115620959A